Comparison of the learning curves for robotic left and right hemihepatectomy: A prospective cohort study. (September 2020) - Liu, Qu; Zhang, Tao; Hu, Minggen; Zhao, Zhiming; Zhao, Guodong; Li, Chenggang; Zhang, Xuan; Lau, Wan Yee; Liu, Rong
Abstract: Objective: Robotic hepatectomy has been continuously improving and shown to be safe and reliable. The learning curve of robotic hemihepatectomy is required which enable beginners to benefit from previous experience. The aim of this study was to assess the learning curve of robotic left (RLH) and right hemihepatectomy (RRH) in terms of operative time (OT) to determine which procedure has an easier learning curve for beginners. Methods: Data records for each 100 consecutive patients who underwent RLH and RRH between July 2012 and May 2019 were collected prospectively and analyzed retrospectively. The data included demographics, OT, estimated blood loss (EBL), postoperative hospital stay (PHS), and rates of morbidity and mortality. The cumulative sum method was used to evaluate the learning curve of OT. Results: All patients underwent the RRH and RLH procedure performed by the same surgical team. RRH and RLH learning curve consisted of two phases: the first and second phase. The first phase of RRH included 45 patients, while RLH outcomes were optimized after 35 cases were completed. Compared with the first phase, the mean OT and the median blood loss were decreased significantly in the second phase in both learning curves. No significant decrease in the rates of morbidity and conversion to laparotomy or PHS was observed. Conclusions: This study demonstrated the safety and feasibility of RLH and RRH. The surgeons who previously lacked robotic experience are able to overcome the learning curve for RLH faster than RRH. Highlights: The largest study to assess the learning curves of RLH and RRH. RLH and RRH is safe and feasible. The learning curve for RLH is shorter compared with RRH.